(3Gdabg GdCcHQs - (3GdgGTej GdbQTj GdeWdHj GdTGaYj, CHh YHO Gddg, eMeO Hf EOQjS Hf GdYHGS, (B204 (3gs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... .. (3gPG cJGH PcQfG ajg XhGgQ GdeSGFd aj CUhd GdOjf GdJj dGHO ddecda ef eYQaJgG hGdhbha YdjgG (B... (3hCYQVfG Yf JHSjW GdCOdI bUOG ddJbQjH Ydi GdeHJOF (B...s
(3BNQgG (B:s
.. (3dCfg Ydjg GdUdGI hGdSdGe bGd (B" (3ef SH CUMGHj abO SHfj hef SHfj abO SH Gddg hef SH Gddg aYdjg dYfI Gddg hGdedGFcI hGdfGS CLeYjf (B" (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\26s
(3cTa GdXfhf (B2/1287s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds